Functional traits of seeds dispersed through endozoochory by native forest ungulates. (20th June 2016) - Picard, Mélanie; Chevalier, Richard; Barrier, Rachel; Boscardin, Yves; Baltzinger, Christophe
Abstract: Aims: Zoochory is a prominent dispersal process in a wide range of plant species. However, the extent to which the trait composition of dispersed seed assemblages differs from the regional assemblage remains untested, as does the extent to which sympatric native herbivores disperse traits non‐randomly. Location: Lorris and Montargis forests, central France. Methods: We compared the taxonomic and functional composition of seed assemblages dispersed by three wild ungulates to the characteristics of the regional flora in an agro‐forested landscape. We collected roe deer ( Capreolus capreolus ), red deer ( Cervus elaphus ) and wild boar ( Sus scrofa ) faeces in two forests, and subjected the samples to germination under controlled conditions. We first examined how different vectors influence the composition of the dispersed plant assemblages by comparing abundance and species richness of the seedlings emerging from the faeces of the three ungulates. We then compared the functional characteristics of the dispersed pool with those of the regional flora in a multivariate functional space built from 20 relevant plant traits. Results: A total of 754 seedlings and 46 plant species germinated from 300 faeces samples, with higher plant species richness and abundance for red deer faeces. All three ungulates widely use forest habitat, but the proportion of non‐forest plants was higher in red deer and wild boar faeces than in the regional species pool. Traits such as seed shape, seed size or seed bank longevity affected dispersal probability, but their effects were overshadowed by habitat effects. Conclusions: Endozoochory acts as an indirect functional filter, filtering species according to the vectors' feeding habitat. This could affect the composition of forest plant communities by allowing plants from open habitats to colonize forested areas. Abstract : A seedling of Chenopodium album that germinated in faeces. Photo © Mélanie Picard. We tackle here a plant‐animal interaction overlooked in plant community dynamics. We compared the functional traits of plants dispersed by three native ungulates through endozoochory to those of the regional flora. We show that endozoochory applies a biotic filter on plant community through vector's feeding habitat preferences, allowing plants from open habitats to colonize forested areas.